HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN PADA WANITA USIA SUBUR YANG MELAKUKAN PAP SMEAR - Sari, Rinda Intan (JURNAL KESEHATAN INDRA HUSADA, 2024)
Women of reproductive age need to pay attention to their reproductive health, as neglecting it increases the risk of cervical cancer. One preventive measure for cervical cancer is screening through pap smears. Women’s low awareness and lack of interest in undergoing pap smears for prevention and early detection of cervical cancer are influenced by factors such as lack of family support and anxiety related to the pap smear procedure. This research aims to determine the relationship between family support and anxiety in women of reproductive age undergoing pap smears at SMC Telogorejo Hospital. This quantitative research was conducted using a cross-sectional approach. The sample consisted of 79 women of reproductive age at SMC Telogorejo Hospital, calculated using the Slovin formula and selected through purposive sampling. The instruments used were family support and anxiety measurement tools. The results showed that family support for women of reproductive age who had pap smears at SMC Telogorejo Hospital was sufficient (65.8%). The level of anxiety in these women was moderate (48.1%). There is a significant correlation between family support and anxiety in women of reproductive age undergoing pap smears at SMC Telogorejo Hospital (p-value = 0.000). The findings suggest that family support can play a crucial role in reducing anxiety for women of reproductive age undergoing pap smears. It is hoped that the results of this research can enhance nurses’ knowledge and involvement in forming support systems to reduce anxiety for these women.